2014
DOI: 10.3389/fncel.2014.00223
|View full text |Cite
|
Sign up to set email alerts
|

Inward rectifier potassium (Kir) current in dopaminergic periglomerular neurons of the mouse olfactory bulb

Abstract: Dopaminergic (DA) periglomerular (PG) neurons are critically placed at the entry of the bulbar circuitry, directly in contact with both the terminals of olfactory sensory neurons and the apical dendrites of projection neurons; they are autorhythmic and are the target of numerous terminals releasing a variety of neurotransmitters. Despite the centrality of their position, suggesting a critical role in the sensory processing, their properties -and consequently their function- remain elusive. The current mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 110 publications
0
14
0
Order By: Relevance
“…Currently, behavioral and olfactory impairment under simulated OA is thought to be caused by alteration of GABA receptor modulation of internal acid-base homeostasis ( Nilsson et al, 2012 ; Chivers et al, 2014 ; Clements and Hunt, 2015 ; Regan et al, 2016 ; Schunter et al, 2016 , 2018 ), leaving the potential impacts of neurotransmitter content largely overlooked. In addition, though it has been shown that upon stimuli, both GABA and ACh will be released into mitral cells, where nerve cells located on the olfactory bulb receive information from the olfactory receptor, indicating essential roles of both GABA and ACh in transmitting olfactory neural signals ( Elaagouby and Gervais, 1992 ; Liu et al, 2013 ; Borin et al, 2014 ; Tatti et al, 2014 ), little is known about the response of ACh to elevated p CO 2 . Therefore, the significant reduction in the in vivo contents of both GABA and ACh under elevated p CO 2 detected in the present study not only suggested that ACh along with GABA may participate in the regulation of OA induced behavioral changes, but also indicated a significant interference in the olfactory neural signal transduction pathway in black sea breams under near-future OA scenarios (Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, behavioral and olfactory impairment under simulated OA is thought to be caused by alteration of GABA receptor modulation of internal acid-base homeostasis ( Nilsson et al, 2012 ; Chivers et al, 2014 ; Clements and Hunt, 2015 ; Regan et al, 2016 ; Schunter et al, 2016 , 2018 ), leaving the potential impacts of neurotransmitter content largely overlooked. In addition, though it has been shown that upon stimuli, both GABA and ACh will be released into mitral cells, where nerve cells located on the olfactory bulb receive information from the olfactory receptor, indicating essential roles of both GABA and ACh in transmitting olfactory neural signals ( Elaagouby and Gervais, 1992 ; Liu et al, 2013 ; Borin et al, 2014 ; Tatti et al, 2014 ), little is known about the response of ACh to elevated p CO 2 . Therefore, the significant reduction in the in vivo contents of both GABA and ACh under elevated p CO 2 detected in the present study not only suggested that ACh along with GABA may participate in the regulation of OA induced behavioral changes, but also indicated a significant interference in the olfactory neural signal transduction pathway in black sea breams under near-future OA scenarios (Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, the warming-triggered outward current was blocked by extracellular Ba 2 + , a blocker of Kir channels. Another study of Kir in dopaminergic neurons of the mouse olfactory bulb has shown that Kir is mildly temperature-sensitive, with a Q10 of~1.22 [64], similar to Kir recorded in cardiac ventricular cells (1.28) [65]. An ATP-sensitive Kir channel was reported to have a Q10 of 1.38 [66] while recordings of another ATP-sensitive K + current in cardiac myocytes had a similar Q10 at the 20-30˚C range but a higher Q10 (2.3) at temperatures between 10-20˚C.…”
Section: Plos Onementioning
confidence: 99%
“…Two other small conductances, activated by hyper-polarization, are present in bulbar DA cells, not directly involved in the pacemaking machinery but playing an important role in its modulation: an h-current (Fried et al, 2010 ; Pignatelli et al, 2013 ) and a potassium inward rectifier (KIR) current (Borin et al, 2014 ). Both currents are active at rest, and exert opposite effects on the resting membrane potential, depolarizing the h-current and hyperpolarizing the KIR, governing the resting membrane potential and consequently exerting an important role in controlling the excitability of these cells.…”
Section: Electrophysiology Of Mature Bulbar Da Neuronesmentioning
confidence: 99%
“…To name only a few, the OB receives serotoninergic afferents from the ventral and dorsal raphe nuclei (Araneda et al, 1980 ), noradrenergic input from the locus coeruleus (McLean et al, 1989 ), cholinergic inputs from the nucleus of the horizontal limb of the diagonal band (Zaborszky et al, 1986 ), and histaminergic inputs from hypothalamus (Panula et al, 1989 ). Accordingly, the KIR current is under the influence of a multiplicity of molecular pathways, which can either enhance the current, as it happens with D2, muscarinic, and GABA A receptor agonists, or have the contrary effect, as it is observed with α1, 5-HT and histamine receptor agonists (Borin et al, 2014 ). Contrary to the KIR, the h-current seems to be modulated only by a single neurotransmitter, noradrenaline, which has a profound inhibitory influence on the current (Pignatelli et al, 2013 ).…”
Section: Electrophysiology Of Mature Bulbar Da Neuronesmentioning
confidence: 99%